1997
DOI: 10.1038/sj.bmt.1700841
|View full text |Cite
|
Sign up to set email alerts
|

Non-tunneled catheters for the collection and transplantation of peripheral blood stem cells in children

Abstract: Summary:patients, vascular access problems and low volume of blood are important factors. 7 The collection of PBSC requires venous access which We analyzed the use of non-tunneled (polyurethane, double lumen) central venous catheters (CVCs) for the ensures withdrawal and reinfusion of blood at high flow rates and allows repeated leukapheresis. Here, we analyze our experience of collection procedures following administration of granulocyte colonystimulating factor (G-CSF) using a continuous flow performed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 5 publications
4
31
0
Order By: Relevance
“…Harvest results, efficiency and changes in peripheral blood and serum values after apheresis are comparable or superior to results reported by other groups using different central venous catheters. [5][6][7][8][9] The influence of body size or age on harvest efficiency was neg- Table 5 Side-effects ligible, and the need for additional CVC apheresis placements could be reduced to a minimum. When using tunneled silicone rubber catheters for PBPC harvesting, pitfalls can be prevented by appropriate placement of the catheter tip.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Harvest results, efficiency and changes in peripheral blood and serum values after apheresis are comparable or superior to results reported by other groups using different central venous catheters. [5][6][7][8][9] The influence of body size or age on harvest efficiency was neg- Table 5 Side-effects ligible, and the need for additional CVC apheresis placements could be reduced to a minimum. When using tunneled silicone rubber catheters for PBPC harvesting, pitfalls can be prevented by appropriate placement of the catheter tip.…”
Section: Discussionmentioning
confidence: 99%
“…Madero et al 8 reported on the use of polyurethane CVCs for stem cell apheresis with the Cobe Spectra cell separator in children. Their harvest results were comparable to ours (mean 6.2 × 10 6 CD34 + cells/kg) and they report a mean CD34 harvest efficacy of 42.78%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of standard tunnelled double lumen CVC for leukapheresis in children was advocated by several groups. 4,5,[17][18][19] The CVC size should correspond with the patient's weight and, therefore, the CVC flow capacity could create difficulties in maintaining an interface in very small patients. 4 Tunnelled silicon-based catheters tend to collapse, their flow rate is significantly lower, and the ports are side by side which causes recirculation of drawn and returned (processed) blood, decreasing collection efficacy.…”
Section: Discussionmentioning
confidence: 99%